31ièmes Journées Franco-Belges de Pharmacochimie: Meeting Report - Raphaël Frédérick; Lionel Pochet; Pascal De Tullio; François Dufrasne (MDPI AG, 2017)
The "Journées Franco-Belges de Pharmacochimie" is a recognized two-day annual meeting on Medicinal Chemistry that is renowned for the advanced science presented, conviviality, and outstanding opportunities for senior and young scientists to exchange knowledge. Abstracts of plenary lectures, oral communications, and posters presented during the meeting are collected in this report.